Cardiac Muscle Histopathological Profile in Hypertensive Rats (Doca-Salt) Exposed to A Combination Of Methanolic Extract Of Tea Mistletoe And Mango Mistletoe (CTMMM) - Hakimah, Annisatul Anis; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid (Metamorfosa: Journal of Biological Sciences, 2021)
Some herbs from the parasite group and the Loranthaceae family also act as antihypertensives. This study aims to look at the histopathological profile of the heart in hypertensive rats (DOCA-Salt) exposed to the combination of Methanolic Extract of Benalu Tea and Mango Benalu (EMBTBM) for 14 days using true experimental design method with completely randomized design on 50 rats, divided into 5 controls -), control (+), treatment 1 dose 50 mg / KgBB, treatment 2 doses 100 mg / KgBB and treatment 3 doses 200 mg / KgBB. Each treatment had 5 replications. In analyzing the data used the ANOVA test, one of the methods is JAMOVI with version 1.1.9.0. As for the calculation of cell diameter using the IMAGE J application. The results showed that the histopathological profile of the heart in hypertensive rats (DOCA-Salt) exposed to EMBTBM for 14 days on heart cell necrosis showed very real evidence between the control (+) and control (- ), treatment 1, 2, and 3. This is evidenced by the results of the analysis p-value <0.05, namely 0.002, so it is denied that EMBTBM has an effect on the average number of necrosis of cardiac cells. There is also a significant difference in the number of heart cell diameter of hypertensive rats between the control (+) and control (-) groups, treatment 1, 2, and 3. This is evidenced by the results of the analysis showing a p-value <0.05, namely 0.021, so that it can it is denied that EMBTBM can shrink the diameter of cells in the heart organ. Keywords : Hypertension, Heart, Left Ventricle, Anatomical Histopathology, EMBTBM.